Business group internationalization: choosing a host country according to institutional distance - A. B Gama, Marina; Lana, Jeferson; Calixto, Cyntia Vilasboas; Bandeira-de-Mello, Rodrigo (Review of Business Management, 2016)
Purpose – This research analyzes to what extent committing resources to the internationalization of family business groups is related to the institutional distance of the host country. Design/methodology/approach – We used OLS panel data with fixed effects. Findings – We identified that family business groups decide to internationalize themselves committing fewer resources to countries that present a positive institutional distance, and that are more institutionally developed than the country of origin. On the other hand, when family business groups choose to expand abroad committing more resources, they tend to invest in countries with a negative institutional distance, and that are less institutionally developed than the country of origin. Originality/value – Our main contribution to existing theory on internationalization of family business groups is to test the relationship between the level of resource commitment by family business groups in their international expansion and the institutional distance between the country of origin and the host country.